2007
DOI: 10.1071/he07121
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco control priorities for Arabic speakers: key findings from a baseline telephone survey of Arabic speakers residing in Sydney's south-west

Abstract: Well-designed trials of efficacy for preferred evidence-based strategies, particularly among middle-aged male Arabic-speaking smokers, appear warranted prior to policy development and implementation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 18 publications
1
25
0
Order By: Relevance
“…They also reported that the lack of media campaigns about waterpipe smoking implied that they must be safer [16]. One study from Australia (reported in 2 papers) found that 81% of respondents to telephone surveys among Arab-speaking residents perceived waterpipe smoking as more harmful [59,60]. A study from Johannesburg South Africa found that 53% of high school students using waterpipe think it is less harmful than cigarettes [24].…”
Section: Resultsmentioning
confidence: 99%
“…They also reported that the lack of media campaigns about waterpipe smoking implied that they must be safer [16]. One study from Australia (reported in 2 papers) found that 81% of respondents to telephone surveys among Arab-speaking residents perceived waterpipe smoking as more harmful [59,60]. A study from Johannesburg South Africa found that 53% of high school students using waterpipe think it is less harmful than cigarettes [24].…”
Section: Resultsmentioning
confidence: 99%
“…A study conducted on Arabic speaking adults reported 11% current waterpipe smoking (Additional file 3; Part 5) [13,53]. Waterpipe use was associated with age group 40-59 (relative to >60), and other forms of smoking.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, the prevalence of current waterpipe smoking among university students was high in the Arabic Gulf region (6%),[25] the United Kingdom (8%),[12] the United States (10%), [50] Syria (15%),[9,26-28] Lebanon (28%),[22] and Pakistan (33%)[42]. The prevalence of current waterpipe smoking among adults was the following: Pakistan (6%),[45] Arabic Gulf region (4%-12%), [19,35,36] Australia (11% in Arab speaking adults),[13,53] Syria (9%-12%),[37,38] and Lebanon (15%)[33]. Studies reported high prevalence of group waterpipe smoking in Lebanon (5%), [33] and Egypt (11%-15%) [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Despite the significant achievements by tobacco control measures such as bans on advertising, bans on smoking indoors and increasingly in outdoor public spaces, plain packaging, new and larger graphic health warnings and mass media campaigns for the general population, there is limited evidence for the effectiveness of anti‐tobacco messages among diverse migrant groups in Australia. While implementing health promotion strategies tailored to culturally and linguistically diverse population in Australia, research has also suggested that migrant community specific tobacco control outreach and cessation services are effective strategies to reduce the tobacco consumption . The use of mass media campaigns through television and radio commercials, Internet, print and public relations strategies to reach non‐English‐speaking migrants may also help to decrease their smoking prevalence.…”
Section: Discussionmentioning
confidence: 99%